Umbilical Cord Tissue-Derived Mesenchymal Stem Cells Induce T Lymphocyte Apoptosis and Cell Cycle Arrest by Expression of Indoleamine 2, 3-Dioxygenase - Xiuying Li; Zhuo Xu; Jinping Bai; Shuyuan Yang; Shuli Zhao; Yingjie Zhang; Xiaodong Chen; Yimin Wang (Stem Cells International)
It has been reported that human mesenchymal stem cells are able to inhibit T lymphocyte activation; however, the discrepancy among different sources of MSCs is not well documented. In this study, we have compared the MSCs from bone marrow (BM), adipose tissue (AT), placenta (PL), and umbilical cord (UC) to determine which one displayed the most efficient immunosuppressive effects on phytohemagglutinin-induced T cell proliferation. Among them we found that hUC-MSC has the strongest effects on inhibiting T cell proliferation and is chosen to do the further study. We observed that T lymphocyte spontaneously released abundant IFN-γ. And IFN-γ secreted by T lymphocyte could induce the expression of indoleamine 2, 3-dioxygenase (IDO) in hUC-MSCs. IDO was previously reported to induce T lymphocyte apoptosis and cell cycle arrest in S phase. When cocultured with hUC-MSCs, T lymphocyte expression of caspase 3 was significantly increased, while Bcl2 and CDK4 mRNA expression decreased dramatically. Addition of 1-methyl tryptophan (1-MT), an IDO inhibitor, restored T lymphocyte proliferation, reduced apoptosis, and induced resumption of the cell cycle. In addition, the changes in caspase 3, CDK4, and Bcl2 expression were reversed by 1-MT. These findings demonstrate that hUC-MSCs induce T lymphocyte apoptosis and cell cycle arrest by expressing abundant IDO and provide an explanation for some of the immunomodulatory effects of MSCs.